Estrada de Ferro Caravelas: trilhos pioneiros na trajetória socioeconômica do Sul do Espírito Santo - Ferreira, Cláudia da Silva (2015)
The purpose of this Social History of Political Affairs dissertation is to discuss the relevance of Caravelas Railroad for socio-economic development of the South of the Espírito Santo State. We present a brief historical approach of iron paths in Europe and in the nineteenth-century Brazil. Then we seek to understand the situation of the national economy and the relationship of the coffee economy with the introduction of railways in the national and Espírito Santo’s scenarios. Also presenting the railroads implamentation’s difficulties in the state scenario and analyze the reasons why the first railway section have been built in the Espírito Santo’s southern region. Finally, we distinguished the importance of the Estrada road on the region’s economic development scenario, under an approach that encompasses economic and social aspects; the impact of the Caravelas Railroad’s implementation and its annexation to the Leopoldina Railway Company, expanding the railway section linking Itapemirim to Alegre and later Espera Feliz. We used official documents and periodicals of the time as main sources, with the methodological approach that seeks to analyze the discourse present in these sources.